The Figure of The Prophet Idris As The Falak Science’s Inventor on Bible, Gospels and Torah (Islamic Astronomy Approach) - Azkarrula, Youla Afifah; Basithussyarop, M (Azimuth: Journal of Islamic Astronomy, 2025)
Prophet Idris was the first man to write Falak with Qalam and taught astrology. Prophet Idris pbuh had a life that was still contemporaneous with prophet Adam as. In addition, the explanation of the Prophet Idris pbuh found in the earlier books up to the Qur'an. As for the books that explain about the Prophet Idris pbuh are Zabur, the Torah, the Gospels and the Qur'an. Over time, the Bible found in the Jewish teachings was united with the teachings of the Christian gospel so that it was called the Bible. Bible consists of the Old Testament which contains the Torah and the New Testament which contains the canonical gospel. Basically, the Qur'an does not directly explain the descendants or nasab of the Prophet Idris pbuh. The explanation of the nasab of the Prophet Idris is explained by the Torah, the Gospels and the Bible with reference to the name Enoch. This is because Idris' name in Hebrew is Enoch. Therefore, to get an explanation of the Prophet Idris, we can refer to the books, namely the Torah, the Gospels and the Bible.